Beyond the Big Five: Does grit influence the entrepreneurial intent of university students in the US? - Nikolaus T. Butz; Sheila Hanson; Patrick L. Schultz; Marissa M. Warzynski (Journal of Global Entrepreneurship Research, 2018)
The purpose of this study was to explore the relationship between grit and entrepreneurial intent. Grit involves maintaining effort and interest in the pursuit of long-term goals, despite adversity, stagnation, or failure. Entrepreneurial intentions are a well-established indicator that represents an individual's conscious determination to start a new business. Secondary variables included the personality traits measured in the Big Five model (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism). Survey data were collected from over 500 undergraduate students at a Midwestern university in the United States. The results confirmed that there was a strong positive association between grit and entrepreneurial intentions. Furthermore, independent samples t-tests revealed that high grit students showed greater entrepreneurial intent than low grit students. The data also indicated that grit fully mediated the predictive effect of conscientious and neuroticism on entrepreneurial intent. Overall, a better understanding of the influence of grit on entrepreneurial intent, given the presence of various diverse personality constellations, may help inform educators in preparing and delivering course content. The influence of grit may reduce the failure rate of new and young businesses launched by college-educated entrepreneurs.
Keywords: 650; Grit; Big Five personality; Entrepreneurship; Entrepreneurial intent; Entrepreneurial education